P3.171* Sexually transmitted infections (STI) among youth with perinatal HIV infection. (13th July 2013) - Pathela, P.; Braunstein, S.; Shepard, C.; Schillinger, J.
Abstract : Background: With antiretroviral therapy (ARV), children who were perinatally infected with HIV (PHIV) are now reaching adolescence/young adulthood. A few studies have described their self-reported sexual behaviours, but none measured the incidence of STI (objective markers of risky behaviour) among PHIV youth. Methods: Separately maintained New York City (NYC) HIV and STI surveillance registries were matched using a deterministic algorithm; the matched dataset contained HIV/AIDS cases reported since 1981 (including retrospectively-identified cases), and STI reported from 2000-June 2010. We calculated incidence of having STI during 2000–2009 (chlamydia, gonorrhoea and early syphilis combined) among the cohort of PHIV individuals born between 1976 and 1987, diagnosed with HIV before age 13, and alive as of 12/31/1999. Additionally, the STI case rate among all PHIV between ages 13–24 during 2000–2009 was compared to that for the NYC population of the same ages. Results: Among 425 PHIV aged 13–19 (n = 409) and 20–24 (n = 16) at start of the 10-year period, 51 (12%) were diagnosed with ≥ 1 STI. Incidence was 1.3/100 person-years. There were 117 diagnoses among 51 PHIV; 25 (49%) had an STI on 2 or more occasions. Incidence was significantly higher among females (2.1/100 person-years; 95% CI, 1.5–2.9) versus males (0.7/100, 000 person-years; 95% CI, 0.4–1.1), and elevated among black PHIV persons (1.9/100 person-years; 95% CI, 1.3–2.6). The PHIV case rate (28, 471/100, 000 persons) was 12% higher than the general population rate (25, 290/100, 000). Conclusions: We documented substantial risk of STI among PHIV, which exceeds risk among other youth. True incidence may be higher than measured if PHIV had not initiated sexual activity as of our follow-up period. All sexually active youth should receive regular STI screening and education; because STI risk behaviours place partners at risk for HIV, PHIV should additionally get interventions around ARV adherence and HIV disclosure. PHIV in HIV care have unique opportunities for such prevention.